Oil and food prices co-integration nexus for Indonesia: a non-linear autoregressive distributed lag analysis - Abdlaziz, Rizgar Abdlkarim; Abdul Rahim, Khalid; Peter, Adamu (EconJournals, 2016)
This paper examines the relationship between the prices of oil and food price for Indonesia using non-linear autoregressive distributed lag (NARDL) method. The bound test for co-integration for the NARDL model shows the evidence of co-integration between food price, growth rate of gross domestic product and oil price. The estimated NARDL for the oil price in domestic currency provides strong evidence of long- and short-run co-integration between food and oil price when the latter increases while the relations for oil price reduction is not present and insignificant. The estimators of positive change in oil price model measured in US Dollar are significant in our study.